2018
DOI: 10.1111/jace.15544
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity in Si3N4 ceramic with the addition of Y2Si4N6C

Abstract: Si3N4 ceramic was densified at 1900°C for 12 hours under 1 MPa nitrogen pressure, using MgO and self‐synthesized Y2Si4N6C as sintering aids. The microstructures and thermal conductivity of as‐sintered bulk were systematically investigated, in comparison to the counterpart doped with Y2O3‐MgO additives. Y2Si4N6C addition induced a higher nitrogen/oxygen atomic ratio in the secondary phase by introducing nitrogen and promoting the elimination of SiO2, resulting in enlarged grains, reduced lattice oxygen content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 44 publications
(171 reference statements)
0
6
0
Order By: Relevance
“…S3, ESI†). 46 First, silane coupling agents (KH-570) were modified onto the surface of n -Si 3 N 4 particles (Fig. S4, ESI†) to build a “molecular bridge” between the interfaces of inorganic ceramic particles and organic substances, which could greatly reduce the agglomeration of n -Si 3 N 4 particles in the subsequent organic precursor system.…”
Section: Resultsmentioning
confidence: 99%
“…S3, ESI†). 46 First, silane coupling agents (KH-570) were modified onto the surface of n -Si 3 N 4 particles (Fig. S4, ESI†) to build a “molecular bridge” between the interfaces of inorganic ceramic particles and organic substances, which could greatly reduce the agglomeration of n -Si 3 N 4 particles in the subsequent organic precursor system.…”
Section: Resultsmentioning
confidence: 99%
“…Si 3 N 4 ceramics have excellent comprehensive properties, such as high strength, high hardness, wear resistance, oxidation resistance, thermal shock resistance, and chemical corrosion resistance, which is considered one of the most promising industrial structural ceramics. [1][2][3][4][5] However, the inherent brittleness of Si 3 N 4 ceramics also limits the reliability of applications where brittle fractures occur at the crack propagation, resulting in catastrophic damage. Therefore, improving the fracture toughness of Si 3 N 4 ceramics remains one of the most critical issues.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, MgO, Al 2 O 3 , and Y 2 O 3 are used to form phases such as SiAlON, MgSiO 4 , and MgSiO 3 [ 37 , 38 ]. In addition to the listed materials, other additives such as MgSiN 2 , YbF 3 , and Y 2 Si 4 N 6 C have been proposed to increase the nitrogen/oxygen ratio [ 33 , 39 ]. Furthermore, Tatami et al [ 40 ] reported that a joint addition of AlN and TiO 2 with sintering aids resulting in TiN microstructures in Si 3 N 4 ceramics improves the fracture toughness the sintered ceramics.…”
Section: Introductionmentioning
confidence: 99%